If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(3a) = 8x + -6 Remove parenthesis around (3a) f * 3a = 8x + -6 Reorder the terms for easier multiplication: 3f * a = 8x + -6 Multiply f * a 3af = 8x + -6 Reorder the terms: 3af = -6 + 8x Solving 3af = -6 + 8x Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Divide each side by '3f'. a = -2f-1 + 2.666666667f-1x Simplifying a = -2f-1 + 2.666666667f-1x
| 2a+b=5a+8b | | (-4)(-3)(-2)= | | 20/28=5/x | | 7n^3+49n=0 | | 3x+4=6x+8 | | 3(2+q)+15=q | | xsquared-5x=9 | | 1x+7y=36 | | f(x)=5x^5+x^4-27x^3-13x^2+134x+120 | | 3(-1/2)(-2/5 | | 0.2x+0.8= | | -4y=168 | | 0.5x+10=16 | | (x+7)+(3x-7)= | | 2/3•4 | | 25/135=x/27 | | 6y-=27-y | | v+16=2v | | 0.1d+0.3(d-7)=8.55 | | (4/7)x(4/8) | | 1/2x-13 | | -6-2(6n+4)= | | H=-3t^2+90t | | 6.4r-2.9r=r | | 7ln(9x)=35 | | -21+2n=1-(1-9n) | | 2x+2-x+2x=3x-3+10-x | | -4(4n+1)+3= | | 32-8=8-x | | y^2+12x+4y-32=0 | | 15x-15=45 | | 35x+100=240 |